Genetic diversity of the endangered black-handed spider monkey Ateles geoffroyi (Primates: Atelidae) in a fragmented landscape of El Salvador - Zaldaña-Orantes, Karla; Sánchez-Trejo, Lucía; Girón-Galván, Luis; Rodríguez, Melissa E.; Nuñez, Genuar; Gutiérrez-Espeleta, Gustavo (Neotropical Primates, 2021)
Spider monkeys (genus Ateles) are distributed across rainforests from southern Mexico to northern Bolivia, but at risk of extinction across much of their range. Like most members of the genus, the black-handed spider monkey, or the Central American spider monkey, Ateles geoffroyi is particularly vulnerable to anthropogenic threats, due to its inability to persist in disturbed and/or isolated forest patches and is categorized as “Endangered” by the IUCN. Within its range in El Salvador, the smallest country in Central America, the spider monkey has now been restricted to isolated patches of semi-deciduous forests, including four fragments that lie within a disturbed agricultural landscape in Jiquilisco Bay, in Southeast El Salvador. We analyzed 73 noninvasive fecal samples from spider monkeys in this region, and we were able to identify 55 individuals. We evaluated the genetic diversity and structure of the four populations using microsatellite markers. Our results show higher observed than expected heterozygosity, but low genetic diversity compared to published data on other spider monkey populations (Ho = 0.50 – 0.57 and He = 0.39 – 0.51; allelic richness with rarefaction = 2.71 – 3.22; private alleles with rarefaction = 0.18 – 0.61). We also found significant differentiation across fragments (Fst = 0.2, P<0.001) and two genetically different groups. These findings suggest the need for conservation action to reconnect forest patches, to improve the unfavorable situation of the only non-human primate in El Salvador.